Caracterização clínica e funcional de indivíduos com doença de Parkinson com dor lombar - André Luis Silveira Barezani (2019)
INTRODUCTION: Pain is a very prevalent symptom in Parkinson's disease (PD), mainly musculoskeletal and in the lumbar region of the spine. However, little is known about the impact of low back pain on the functional capacity and quality of life of individuals with PD. OBJECTIVE: To evaluate the presence of low back pain in individuals with PD and its impact on the functional capacity and quality of life of these patients. MATERIALS / METHODS: Patients with idiopathic PD from the Movement Disorders outpatient clinic, Santa Casa de Belo Horizonte Hospital, were invited to answer a questionnaire on sociodemographic and clinical characteristics. Patients with low back pain were evaluated for cognitive and affective functions, signs and symptoms of PD, stage of disease, pain intensity and their impact on functional capacity and quality of life. RESULTS: One hundred and fifteen (72 men, 62.6%) patients with mean age of 68.0 (± 11.8) years and mean disease duration of 6.8 (± 4.9) years participated in the study. Pain was reported in 95 (82.6%) patients and 67 (58.2%) had chronic low back pain (over three months). Forty patients (70 ± 11.1 years and 7.4 ± 5.4 years of PD) in the 1.5 to 3 stages of PD were evaluated. Worst depressive symptoms (rs= 0.434, p= 0.005), higher scores in section II (rs= 0.554, p<0.001), in section III (rs= 0.390, p= 0.013) and total score (rs= 0.493, p= 0.001) 0.001) of the Unified Parkinson's Disease Rating Scale (UPDRS), more advanced stage of the disease (rs= 0.493, p= 0.001) and the absence in the contraction of transversus abdominis (rs= 0.333, p= 0.042) determined greater difficulty to perform activities of daily living at home or at work evaluated by the Roland-Morris Questionnaire. In the UPDRS III, rigidity score negatively influences the amplitude of trunk flexion (rs= -0.355, p= 0.024). The greater the intensity of pain and the level of difficulty to perform activities of daily living at home or at work directly influence the perception in several domains of the Quality of Life Questionnaire (PDQ-39). CONCLUSION: The present study indicates a high prevalence of pain, with the lumbar region being most affected. Higher pain intensity, worse depressive symptoms, greater severity and stage of PD disease, and absence of transverse muscle contraction resulted in greater functional disability. Quality of life was directly affected by pain intensity and functional disability.